(untitled) (Acta Entomologica Serbica, 2021)
The fauna of butterflies in Serbia is richer for another species - Tarucus balkanicus (Freyer, 1845). During the research of the Landscape of Outstanding Features of the "Valley of Pčinja", on August 3rd and 4th, a total of 6 individuals of this species were recorded at the site of Čivčija. The feeding plant of this species is Paliurus spina-christi, on the basis of which the popular Serbian name for T. balkanicus – “dračac” was proposed.